The current and future role of magnetic resonance imaging in prostate cancer detection and management - Radtke, Jan Philipp; Teber, Dogu; Hohenfellner, Markus; Hadaschik, Boris (Translational andrology and urology, 2015)
Purpose: Accurate detection of clinically significant prostate cancer (PC) and correct risk attribution are essential to individually counsel men with PC. Multiparametric MRI (mpMRI) facilitates correct localization of index lesions within the prostate and MRI-targeted prostate biopsy (TPB) helps to avoid the shortcomings of conventional biopsy such as false-negative results or underdiagnosis of aggressive PC. In this review we summarize the different sequences of mpMRI, characterize the possibilities of incorporating MRI in the biopsy workflow and outline the performance of targeted and systematic cores in significant cancer detection. Furthermore, we outline the potential of MRI in patients undergoing active surveillance (AS) and in the pre-operative setting. - Materials and methods: An electronic MEDLINE/PubMed search up to February 2015 was performed. English language articles were reviewed for inclusion ability and data were extracted, analyzed and summarized. - Results: Targeted biopsies significantly outperform conventional systematic biopsies in the detection of significant PC and are not inferior when compared to transperineal saturation biopsies. MpMRI can detect index lesions in app. 90% of cases as compared to prostatectomy specimen. The diagnostic performance of biparametric MRI (T2w + DWI) is not inferior to mpMRI, offering options to diminish cost- and time-consumption. Since app 10% of significant lesions are still MRI-invisible, systematic cores seem to be necessary. In-bore biopsy and MRI/TRUS-fusion-guided biopsy tend to be superior techniques compared to cognitive fusion. In AS, mpMRI avoids underdetection of significant PC and confirms low-risk disease accurately. In higher-risk disease, pre-surgical MRI can change the clinically-based surgical plan in up to a third of cases. - Conclusions: mpMRI and targeted biopsies are able to detect significant PC accurately and mitigate insignificant PC detection. As long as the negative predictive value (NPV) is still imperfect, systematic cores should not be omitted for optimal staging of disease. The potential to correctly classify aggressiveness of disease in AS patients and to guide and plan prostatectomy is evolving.